Alternative splice variants of AID are not stoichiometrically present at the protein level in chronic lymphocytic leukemia. Issue 7 (15th April 2014) - Rebhandl, Stefan; Huemer, Michael; Zaborsky, Nadja; Gassner, Franz Josef; Catakovic, Kemal; Felder, Thomas Klaus; Greil, Richard; Geisberger, Roland
<x xml:space="preserve">Abstract</x> Activation‐induced deaminase (AID) is a DNA‐mutating enzyme that mediates class‐switch recombination as well as somatic hypermutation of antibody genes in B cells. Due to off‐target activity, AID is implicated in lymphoma development by introducing genome‐wide DNA damage and initiating chromosomal translocations such as c‐myc/IgH. Several alternative splice transcripts of AID have been reported in activated B cells as well as malignant B cells such as chronic lymphocytic leukemia (CLL). As most commercially available antibodies fail to recognize alternative splice variants, their abundance in vivo, and hence their biological significance, has not been determined. In this study, we assessed the protein levels of AID splice isoforms by introducing an AID splice reporter construct into cell lines and primary CLL cells from patients as well as from WT and TCL1tg C57BL/6 mice (where TCL1 is T‐cell leukemia/lymphoma 1). The splice construct is 5′‐fused to a GFP‐tag, which is preserved in all splice isoforms and allows detection of translated protein. Summarizing, we show a thorough quantification of alternatively spliced AID transcripts and demonstrate that the corresponding protein abundances, especially those of splice variants AID‐ivs3 and AID‐ΔE4, are not stoichiometrically equivalent. Our data suggest that enhanced proteasomal degradation of low‐abundance proteins might be causative for this discrepancy.